The Slovenian community in Croatia during the Covid-19 pandemic - Riman, Barbara (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2020)
The article analyses the impact of the Covid-19 pandemic on the life and work of the Slo-venian community in Croatia, focusing on the attitude of the Republic of Slovenia towards the members of such community and the challenges they encountered in maintaining contacts with Slovenia. The article studies Slovenian and Croatian media reports as well as documents published in the Official Gazette of the Republic of Slovenia. In addition, it examines data obtained from interviewees who live in the border area and/or are active members of the Slovenian community in Croatia. The testimonies largely relate to changes of the border regime that have affected the interviewees' private and professional life. The processes resulting from the measures adopted to tackle the pandemic have indeed left a deep imprint on the lives of the members of the Slovenian community in Croatia.
Keywords: čezmejno sodelovanje; državne meje; Hrvaška; mejni režim; pandemija covid 19; Slovenci; slovensko-hrvaška meja